PENEGAKAN HUKUM TINDAK PIDANA PEMILIHAN UMUM KEPALA DAERAH DI WILAYAH HUKUM KEPOLISIAN RESOR KABUPATEN KAMPAR - Alfatah, Alfarouq; Indra, Mexsasai; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The holding of elections is held every five years, this is reflected in Article 22E paragraph (1) of the1945 Constitution which states that "General Elections are carried out directly, publicly, freely, secretly,honestly and fairly every five years". Quality elections are influenced by many factors. Tight competitionbetween advanced regional head candidates can create the potential for various fraudulent practices so thatthey can damage the real purpose, which is honest and fair elections and obtain pure and quality results.The purpose of this thesis is to find out the law enforcement of post-conflict local election actions and to findout the factors that cause the crime of post-conflict local election and in the police law area of Kamparregency resort.This type of research can be classified in the type of sociological juridical research, because in thisstudy the author immediately conducts research on the location or place under study in order to provide acomplete and clear picture of the problem under study. This research was conducted in the jurisdiction ofKampar Regency, while the population and samples were all parties related to the problems examined inthis study, data sources used, primary data, secondary data, and tertiary data, data collection techniques inthis study with interviews and literature review.From the results of the research that the author did, it can be concluded, First, the law enforcementof criminal acts of post-conflict local election in the resort area of Kampar regency police is to establish anintegrated law enforcement center (Gakkumdu center). The two factors causing the post-conflict localelection crime in the Kampar regency police jurisdiction are not understanding the regulations regardingthe stages of the election, the lack of socialization by the organizers, the rigorous electoral competitionagainst regional heads, and economic factors.Keywords: Law Enforcement - Criminal Offense- Post-conflict Local Election